MoS2/MoO2 nanosheets anchored on carbon cloth for high-performance magnesium- and sodium-ion storage. (20th April 2023) - Wu, Hui; Xiong, Zhennan; Mao, Yiyang; Zhang, Huihui; Hu, Yingying; Shen, Jun; Wang, Baofeng; Yu, Xuebin
Highlights: A new MoS2 /MoO2 hybrid nanosheets embedded in CC composite had been designed. The MoS2 /MoO2 /CC composite was prepared by a facile hydrothermal synthesis. The MoS2 /MoO2 /CC binder free electrode delivered significant magnesium and sodium storage behavior. The unique structural merits contributed to the superior electrochemical performance. Abstract: Developing new types of rechargeable metal-ion batteries beyond lithium-ions, including alkaline ion (such as Na +, K + ) and multivalent ion (such as Mg 2+, Zn 2+, Ca 2+ and Al 3+ ) batteries, is progressing quickly towards large-scale energy storage systems. However, the major obstacle to their large-scale applications has been a lack of appropriate electrode materials with reversible metal ions insertion/extraction behavior, resulting in inferior electrochemical performance. Here we develop a well-designed MoS2 /MoO2 hybrid nanosheets anchored on carbon cloth (MoS2 /MoO2 /CC) as electrode materials. This rational design can effectively shorten ion diffusion distance, increase electric conductivity of the electrode, and buffer volume change. Benefiting from the synergistic effect of structural and compositional features, the MoS2 /MoO2 /CC electrode exhibits high initial reversible capacities (326 mA h g −1 at 0.1 A g −1 in magnesium-ion storage; 1270 mA h g −1 at 0.1 A g −1 in sodium-ion storage), excellent rate capacities (57 mA h g −1 at 10 A g −1 in magnesium-ion storage; 335 mA h g −1 at 5 A g −1 in sodium-ion storage) and long-term cycling stability (105 mA h g −1 after 600 cycle at 1 A g −1 in magnesium-ion storage; 208 mA h g −1 after 600 cycles at 5 A g −1 in sodium-ion storage). We expect that the multi-engineering strategy will provide some valuable insights for the development of other advanced electrode materials for high-performance metal-ion batteries.